2015
DOI: 10.1038/sc.2015.138
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of unexpected postural changes during robot-assisted gait training in paraplegic patients

Abstract: Study design: This is a retrospective study. Objectives: The objectives of this study were to categorize unexpected postural changes (UPCs) during gait training in paraplegic patients with wearable gait-assist robots, to reveal the incidence of the UPC and its time-dependent changes during initial gait training period and to investigate neurological level-specific differences. Setting: This study was conducted in Fujita Health University, Aichi, Japan. Methods: We investigated five patients (46.2 ± 14.6 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Second, one person stayed behind him/her at all times since falling over backward was reported to occur most commonly during gait with WPAL. 22 Third, the training emphasized well-timed forward movement of the walker essential to avoiding falls due to unexpected postural changes. No falls were reported during the course of this study, nor were there complications such as pressure sores, cardiovascular stresses, pain or musculoskeletal problems.…”
Section: Discussionmentioning
confidence: 99%
“…Second, one person stayed behind him/her at all times since falling over backward was reported to occur most commonly during gait with WPAL. 22 Third, the training emphasized well-timed forward movement of the walker essential to avoiding falls due to unexpected postural changes. No falls were reported during the course of this study, nor were there complications such as pressure sores, cardiovascular stresses, pain or musculoskeletal problems.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the unstable autonomic control after a SCI, these individuals have an increased risk of developing heart disease and stroke, with cardiovascular and respiratory dysfunctions being among the leading causes of death for people with SCI (30). This increased mortality risk means that early recognition and accurate management of cardiovascular dysfunctions are crucial to reducing their secondary risk profile (23,36,38).In this review, studies considering cardiovascular changes in HR and BP indicated no significant changes in HR with RLT interventions and reported variable BP changes within and post RLT. Two studies reported a significant increase in BP post-RLT (7,24), while the other 2 studies showed no changes across the intervention (13,20).…”
Section: Cardiovascular Demandmentioning
confidence: 99%
“…The remaining 21 studies did discuss potential biases, with 5 studies acknowledging competing interests, whereas the other 16 had none to declare. However, 9 of these 16 studies declared incorrectly, as they did not acknowledge the conflicts of interest related to being financially supported (11,13) and receiving salaries from exoskeleton companies (14,19,21,22,36) or performing the study to achieve FDA clearance for the exoskeleton company (12,24). It is relevant to note that due to the high cost of the robotic devices, subsidization is often required from the relevant companies for access and/or maintenance of the devices.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In the present study, patients with C5-C6 lesions did not reach an FAC score of 4 using the WPAL, on equality with using other WREs. However, patients with C7 lesions, even with motorcomplete SCIs, reached an FAC score of 4 even in patients with motor-complete because the WPAL has a high standing stability, which is a structural characteristic similar to medialtype orthoses (Saitoh et al, 1996;Tanabe et al, 2013b;Koyama et al, 2016).…”
Section: Discussionmentioning
confidence: 99%